Design Elements and Electrical Performance of a Bifacial BIPV Module. (3rd November 2016) - Kang, Jun-Gu; Kim, Jin-Hee; Kim, Jun-Tae
Abstract : Bifacial BIPV systems have great potential when applied to buildings given their use of a glass-to-glass structure. However, the performance of bifacial solar cells depends on a variety of design factors. Therefore, in order to apply bifacial solar cells to buildings, a bifacial PV module performance analysis should be carried out, including consideration of the various design elements and reflecting a wide range of installation conditions. This study focuses on the performance of a bifacial BIPV module applied to a building envelope. The results here show that the design elements of reflectivity and the transparent space ratio have the greatest impact on performance levels. The distance between the module and the wall had less of an impact on performance. The bifacial BIPV module produced output up to 30% greater than the output of monofacial PV modules, depending on the design elements. Bifacial BIPV modules themselves should have transparent space ratios of at least 30%. When a dark color is used on the external wall with reflectivity of 50% or less, bifacial BIPV modules with transparent space ratios of 40% and above should be used. In order to achieve higher performance through the installation of bifacial BIPV modules, design conditions which facilitate reflectivity exceeding 50% and a transparent space ratio which exceeds 30% must be met.